Supporting and contaminating femininity within the aura of gender equality - Pétursdóttir, Gyða Margrét (School of Social Sciences, 2023)
Femininity is socially constructed and takes different shapes in different social contexts. The article discusses emphasized femininity, a concept related to Connell‘s hegemonic masculinity, in the labour market and private life. The opposite of emphasized femininity is pariah femininity. Both concepts relate differently to the aura of gender equality. The aura of gender equality describes the social process, or phenomena, in which men and women convince themselves that equality reigns despite practical evidence indicating otherwise The analysis is based on an extensive qualitative research project addressing three sectors in the labour market: The City of Reykjavík workplaces, software firms, and fast-food restaurants, a supermarket and a gas station. Interviews were carried out among 48 employees and participant observations were conducted at 11 workplaces. The following question is posed: How does emphasized femininity facilitate women’s subordination? The results show that emphasized femininity is one of the prerequisites for staying within the aura of gender equality while pariah femininity contaminates the relationship between hegemonic masculinity and emphasized femininity and is therefore viewed dimly but is nevertheless able to facilitate real gender equality. Kvenleikinn er félagslega mótaður og birtist með ólíkum hætti í ólíkum aðstæðum. Í greininni er fjallað um birtingarmyndir styðjandi kvenleika, systurhugtak ráðandi karlmennsku, á vinnumarkaði og í einkalífi. Andstæða styðjandi kvenleika; mengandi kvenleiki, er greindur og skoðað hvernig bæði hugtökin tengjast áru kynjajafnréttis með ólíkum hætti. Ára kynjajafnréttis lýsir félagslegu ferli eða fyrirbæri þar sem karlar og konur sannfæra sjálf sig um að jafnrétti ríki þrátt fyrir að raunin sé önnur. Greiningin byggir á umfangsmikilli eigindlegri rannsókn á þremur sviðum á vinnumarkaði: Vinnustöðum Reykjavíkurborgar, hugbúnaðarfyrirtækjum, og skyndibitastöðum, matvöruverslun og bensínstöð. Tekin voru eigindleg viðtöl við 48 starfsmenn og ...